2019
DOI: 10.3390/ijerph16234781
|View full text |Cite
|
Sign up to set email alerts
|

Association between Work-Related Stress and QT Prolongation in Male Workers

Abstract: Background: Work-related stress is a potential cardiovascular risk factor, but the underlying mechanism is not fully explained. The autonomic nervous system control of cardiac function might play a specific role; therefore, monitoring the QT interval in the electrocardiogram can highlight an autonomic imbalance induced by occupational stressors. The aim of our study was to explore the QT interval parameters as early indicators of imbalance of the autonomic cardiac function in relation to work-related stress. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…We appreciate the interest raised by our paper on the association between conditions linked to work-related stress and the prolongation of the QT interval on the electrocardiogram [1]. Alizargar et al, in their commentary [2], raise two main concerns, namely: (1) the operational location would be the main determinant of QT interval prolongation, and (2) one would have to assess Pearson's correlation "before analyzing the assumptions that should be made before such an analysis".…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…We appreciate the interest raised by our paper on the association between conditions linked to work-related stress and the prolongation of the QT interval on the electrocardiogram [1]. Alizargar et al, in their commentary [2], raise two main concerns, namely: (1) the operational location would be the main determinant of QT interval prolongation, and (2) one would have to assess Pearson's correlation "before analyzing the assumptions that should be made before such an analysis".…”
mentioning
confidence: 95%
“…Table 1. Test for the assumption of normality of the distribution of the continuous variables presented in Table 2 of Lecca et al (1). BMI-body mass index; KS-Kolmogorov-Smirnov; SD-standard deviation.…”
mentioning
confidence: 99%
“…We read with interest the article by Lecca et al [1], in which the authors focused on the effects of work-related stress on changes in the QT interval in the routine electrocardiogram (ECG) among workers without overt cardiovascular dysfunction. They also tried to consider some confounders in their analysis.…”
mentioning
confidence: 99%
“…However, the main factor is age. Lecca et al [1] had excluded the people that had some of the these conditions so they could not interfere with the conclusion of their study. They also showed that the observed effects of age in the correlation analysis disappeared when they controlled for some factors, such as operating location, physical activity, systolic blood pressure (SBP), age, education, and alcohol intake; yet, they concluded that "age was a clear contributing factor in QTc and QTi prolongation in our study", and compared their results to other studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation